Regional Disaster Management Agency Strategy In Flood Disaster Mitigation In Bontang City, East Kalimantan Province - Remon Samosir; Mujahidin; Lalu Ahmad Murdhani (Yayasan Hisnul Muslim Lombok, 2024)
The research entitled